Midwives' and nurses' knowledge and confidence level in relation to obesity and adiponectin in early pregnancy in Hospital Universiti Sains Malaysia (HUSM}: a comparative study - Vi, Lai Sue (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
Adiponectin have been implicated in both the physiological adaptation to pregnancy and obstetrical complications while low plasma adiponectin has been identified as a risk factor for type 2 diabetes. Knowledge on adiponectin level and its association with obesity and gestational diabetes mellitus are important in obstetric care. To the researcher knowledge, there have been no published studies paid to explore midwives' and nurses' knowledge and confidence level in relation to obesity and adiponectin in early pregnancy in Malaysia. The aim of this study was to explore the midwives' knowledge and confidence level in relation to obesity and adiponectin in early pregnancy in maternity units, Hospital Universiti Sains Malaysia (HUSM) and to compare with that of nurses working in the same maternity units. A cross sectional survey on all nursing staffs (nurses and midwives) (n=91) in maternity unit HUSM was done using a self-administered structured questionnaire. Data was analyzed using the Statistical Package Social Science (SPSS) software version 18.0. Sixty-seven were midwives (74%) and 24 were nurses (26%). All nurses and midwives in maternity unit agreed that obesity increase the adverse health outcome to pregnant women. Independent t-Test revealed that midwives were more knowledgeable on relation of adiponectin and obesity in early pregnancy, with a mean score of 9.9, compared to nurses, with mean scores of 6.58 (p<0.05). Using the One-way ANOVA test, the result also shown that the nursing staffs who have higher working experience have higher knowledge score (11.67) on relation of adiponectin and obesity, compared to nursing staffs who have less working experience (p<0.05). There is no association between knowledge score of the nursing staffs in maternity unit with their confidence level in providing care and health teaching (R2=0.032, p>0.05). Majority of the nursing staffs (82.4%) in maternity unit addressed the need of education regarding the relationships between adiponectin and pregnancy. A majority of the nursing staffs (more than 50%) disagree that they have sufficient knowledge regarding the relationships between plasma adiponectin with pregnancy and maternal overweight. This study suggests that the nurses, as compared to midwives, who are also front line healthcare providers lack adiponectin knowledge that is essential for daily practice. This low knowledge may affect their confident level and care given to pregnant women. Although the midwives' knowledge remains relatively higher than nurses, this warrants a need to promote adiponectin knowledge in relation to obesity and early pregnancy among nurses and midwives. Therefore, review should be made in the nursing and midwifery curricula. The results of this study herein presented can serve as the basis to facilitate continuous education and research on adiponectin and its association to obesity and in early pregnancy among other healthcare professionals.